Acoso laboral o Mobbing y el síndrome de Burnout en el personal técnico del Fuerte Militar Miguel Iturralde periodo 2019-2020 - Acaro Castillo, Tatiana del Cisne (2020)
Nowadays the burnout syndrome and the harassment at work or mobbing, have become a problem of great social relevance, due to the fact that they are considered as a harmful factor for the health of the workers. This study aims to determine the relationship between the two variables mentioned. The methodology applied has a quantitative approach, with a descriptive-correlational and transversal design, in which 85 people participated, corresponding to 100% of the male gender, belonging to the Miguel Iturralde Military Fort in the city of Loja. The instruments used were the Cisneros Scale and the Maslach Test, which made it possible to evaluate harassment at work and burnout syndrome, respectively. The results indicate that there is a low prevalence of harassment at work. In the same way it was identified that most of the subject population, presents tendency to develop burnout syndrome. It was also determined that there is no relationship between the two variables. However, it was considered relevant to develop a prevention plan in order to reduce the risks of suffering these phenomena and to improve the mental health of the professionals of the army Key words: Burnout syndrome - Workplace stress - Workplace harassment- mobbing